Relevansi Insidād Bāb al-Ijtihād dalam Ilmu Falak - Zain, Muhammad Fajri Kholili; Asshiddiqy, Robith Addian (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
The Insidād Bāb al-Ijtihād discourse has a huge influence on the paradigm shift of Islamic law in modern times. This discourse say that the study of Islamic law has been finalized and the answers formulated by the imam madhhab, so the exploration of the law afterwards is irrelevant. There are critics who consider that ijtihad is supposed to exist because it is a bridge between the nass (text) and al-waqiʿ (reality). In the study of Falak, ijtihad is deemed necessary to exist because the development of methods, technology, and calculation in it progresses very fast. This raises the need for relevant fiqh laws that accommodate all existing changes. On those grounds, the question arises whether the Insidad Bab al-Ijtihad is relevant if applied in the study of Falak today. Through the method of literature review and descriptive-deductive analysis, it was found that: Insidad Bab al-Ijtihad is not relevant in the realm of Falak studies. The development of the methods and technology in Falak requires the process of ijtihad to exist.